Conectividade e dodiscência no ensino com audiovisual - um estudo das percepções de estudantes e professores da escola básica - Stefanelli, Ricardo (2017)
The objective of this research is to analyze the theoretical and methodological foundations that support pedagogical practices present in the teaching and learning with basic school developed audiovisual, highlighting your condition of active and collaborative method in which explicit theoretically the connectivity and dodiscencia category, as manifested in the theorizing of freiriana base. Methodologically, documentary analysis was performed of the legal provisions on the teaching of the curriculum components of the field of Arts, Communication and Technologies present in the guidelines and Bases for national education (LDBEN 9394/96) and in your subsequent amendment by law nº 13,006, 2014; 9795/99 and 12,603, 2012, besides the PCNs and DCNs on the same components; literature review was made about teaching with audiovisual use in education, particularly for parsing the areas of Art-Education and Educommunication relevant just because they're theorizing considered in structuring of curriculum documents; data was collected through in-depth interviews with the following subjects: three students who attended the course of audiovisual projects in high school; three teachers from Brasilia that also utilize audiovisual in their lessons and a teacher of Belo Horizonte; besides an epistemological circle with 23 students, between 11 to 18 years of age, three State and one federal public schools. It was sought, in the interviews and epistemological circle, the subjects theoretical understanding of their teaching-learning practices with audiovisual was sought, and later, to analyze the statements through the technique of Categorical Analysis, oriented by the categories-synthesis, connectivity and dodiscence, based on the theorizations of authors affiliated with the Frerian pedagogical tradition, in comparison with the theoretical production resulting from the bibliographical revision on teaching using audiovisual. The main conclusion of the study is that teachers and students understand their pedagogical practices with audiovisual as a result of a collective effort involving connectivity and dodiscence, integrating the teacher's learning-teaching knowledge with the students' teaching-learning knowledge, since both complement each other in activities of teaching with the audiovisual in the classroom, providing a more mainstream education and fostering student autonomy.